Preparation and evaluation of buccal bioadhesive films containing clotrimazole - Singh S.; Jain S.; Muthu M.S.; Tiwari S.; Tilak R. (My University, 2025)
Buccal bioadhesive films, releasing topical drugs in the oral cavity at a slow and predetermined rate, provide distinct advantages over traditional dosage forms. The aim of present study was to prepare and evaluate buccal bioadhesive films of clotrimazole for oral candidiasis. The film was designed to release the drug at a concentration above the minimum inhibitory concentration for a prolonged period of time so as to reduce the frequency of administration of the available conventional dosage forms. The different proportions of sodium carboxymethylcellulose and carbopol 974P (CP 974P) were used for the preparation of films. Carbopol was used to incorporate the desired bioadhesiveness in the films. The films were prepared by solvent casting method and evaluated for bioadhesion, in vitro drug release and effectiveness against Candida albicans. In vitro drug release from the film was determined using a modified Franz diffusion cell while bioadhesiveness was evaluated with a modified two-arm balance using rabbit intestinal mucosa as a model tissue. Films containing 5% CP 974P of the total polymer were found to be the best with moderate swelling along with favorable bioadhesion force, residence time and in vitro drug release. The microbiological studies revealed that drug released from the film could inhibit the growth of C. albicans for 6 h. The drug release mechanism was found to follow non-Fickian diffusion. © American Association of Pharmaceutical Scientists 2008.